The Bacterial Microbiome Associated With Arid Biocrusts and the Biogeochemical Influence of Biocrusts Upon the Underlying Soil - Moreira-Grez, B.; Tam, Kang; Cross, Adam; Yong, Jean; Kumaresan, D.; Nevill, Paul; Farrell, M.; Whiteley, A.S. (FRONTIERS MEDIA SA, 2019)
Biocrusts are aggregated crusts that exist on the soil surface of arid environments. They are complex microbial communities comprised of cyanobacteria, lichens, mosses, algae and fungi. Recently, biocrusts have gained significant attention due to their ubiquitous distribution and likely important ecological roles, including soil stabilization, soil moisture retention, carbon (C) and nitrogen (N) fixation, as well as microbial engineers for semi-arid ecosystem restoration. Here, we collected three co-occurring types of biocrust (Cyanobacterial crust, Crustose lichen, and Foliose lichen) and their underlying soil from arid zones within Western Australia. Bacterial microbiome composition was determined through 16S rRNA gene amplicon sequencing to assess the extent of microbiome selection within the crusts versus underlying soil and biogeochemical measures performed to determine whether the crusts had significant impact upon the underlying soil for nutrient input. We determined that the bacterial communities of native biocrusts are distinct from those in their underlying soil, where dominant bacterial taxa differed according to crust morphologies. δ15N revealed that N-fixation appeared most evident in Foliose lichen crust (1.73 ± 1.04‰). Consequently, depending upon the crust type, biocrusts contained higher concentrations of organic C (2 to 50 times), total N (4 to 16 times) and available ammonium (2 to 4 times), though this enrichment did not extend to the soils underneath them. These findings demonstrate that biocrust communities are seemingly islands of biological activity in an arid landscape, uniquely different from their surrounding and underlying soil.